Nanomaterial-induced mitochondrial biogenesis enhances intercellular mitochondrial transfer efficiency - John Soukar; Kanwar Abhay Singh; Ari Aviles; Sarah Hargett; Harman Kaur; Samantha Foster; Shounak Roy; Feng Zhao; Vishal M. Gohil; Irtisha Singh; Akhilesh K. Gaharwar (Proceedings of the National Academy of Sciences, 2025)
Intercellular mitochondrial transfer, the spontaneous exchange of mitochondria between cells, is a recently described phenomenon crucial for cellular repair, regeneration, and disease management. Enhancing this natural process holds promise for developing novel therapies targeting diseases associated with mitochondrial dysfunction. Here, we introduce a nanomaterial-based approach employing molybdenum disulfide (MoS 2 ) nanoflowers with atomic-scale vacancies to stimulate mitochondrial biogenesis in cells to make them mitochondrial biofactories. Upon cellular uptake, these nanoflowers result in a two-fold increase in mitochondrial mass and enhancing mitochondrial transfer to recipient cells by several-fold. This enhanced efficiency of transfer significantly improves mitochondrial respiratory capacity and adenosine triphosphate production in recipient cells under physiological conditions. In cellular models of mitochondrial and cellular damage, MoS 2 enhanced mitochondrial transfer achieved remarkable restoration of cell function. This proof-of-concept study demonstrates that nanomaterial-boosted intercellular mitochondrial transfer can enhance cell survivability and function under diseased conditions, offering a promising strategy for treating mitochondrial dysfunction-related diseases.